Industrialization and modernization based on science technology and innovation: Chinese experience and lessons for Vietnam - Dinh Viet Hoang (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2024)
China is considered one of the countries that has successfully implemented industrialization and modernization based on science, technology and innovation in the world. In Vietnam, facing rapid changes in the world economic, political and social environment, the need to accelerate the process of industrialization and modernization of the country has become more urgent than ever. With the advantage of being a latecomer, Vietnam can completely learn from the experiences of previous countries, especially countries with similar political and cultural institutions like China. This paper will evaluate the process of industrialization and modernization based on science, technology and innovation in China, thereby suggesting lessons for Vietnam in the coming time. Code: 23101201